Factors Affecting Consumer Demand for Premium Rice in Tanjung Pering Village, North Indralaya District Ogan Ilir Regency - Ardha, Sophia Anjani; Purbiyanti, Erni (Sriwijaya Journal of Agribusiness and Biometrics in Agriculture Research, 2023)
households in Indralaya Utara District, Ogan Ilir Regency, 2) analyze the factors that influence consumer demand for premium rice in Indralaya Utara District, Ogan Ilir Regency and 3) analyze the proportion of food expencies and non-food expencies in Indralaya Utara District, Ogan Ilir Regency. This research was conducted in Tanjung Pering Village, North Indralaya District, Ogan Ilir Regency. This location determination was done deliberately with the research method used is the survey method. Datacollection was carried out in May-June 2023. The sampling method used was non- probability sampling, namely the samples were not randomly selected using the purposive sampling method. The research results obtained are: (1) The characteristics of premium rice household consumers consist of housewives who have an average age of 31 years, with the last education level of high school and have a family of 5 people with an average family income of Rp. 4,862,233/month. (2) factors that affect consumer demand for premium rice is Premium Rice Prices, Medium Rice Prices (Substitute Goods), Household Income, and Number of Family Members. (3) And for the results of the average proportion of food expenditure from 30 respondents, it was found that there are 7 people whose food expenditure is less than non-food expenditure and there are 23 people whose food expenditure is greater than non-food expenditure by 77 percent. This means that consumers of premium rice in Tanjung Pering Village have food expenditures that are greater than their non-food